Domain-specific physical activity patterns and cardiorespiratory fitness among the working population: Findings from the cross-sectional German Health Interview and Examination Survey - Thomas Keil; Johannes Zeiher; Maurice Duch; Lars E Kroll; Gert B M Mensink; Jonas D Finger (BMJ Open)
Objectives This study aimed to investigate associations between occupational physical activity patterns (physical work demands linked to job title) and leisure time physical activity (assessed by questionnaire) with cardiorespiratory fitness (assessed by exercise test) among men and women in the German working population.Design Population-based cross-sectional study.Setting Two-stage cluster-randomised general population sample selected from population registries of 180 nationally distributed sample points. Information was collected from 2008 to 2011.Participants 1296 women and 1199 men aged 18–64 from the resident working population.Outcome measure Estimated low maximal oxygen consumption (V˙O2max), defined as first and second sex-specific quintile, assessed by a standardised, submaximal cycle ergometer test.Results Low estimated V˙O2max was strongly linked to low leisure time physical activity, but not occupational physical activity. The association of domain-specific physical activity patterns with low V˙O2max varied by sex: women doing no leisure time physical activity with high occupational physical activity levels were more likely to have low V˙O2max (OR 6.54; 95% CI 2.98 to 14.3) compared with women with ≥2 hours of leisure time physical activity and high occupational physical activity. Men with no leisure time physical activity and low occupational physical activity had the highest odds of low V˙O2max (OR 4.37; 95% CI 2.02 to 9.47).Conclusion There was a strong association between patterns of leisure time and occupational physical activity and cardiorespiratory fitness within the adult working population in Germany. Women doing no leisure time physical activity were likely to have poor cardiorespiratory fitness, especially if they worked in physically demanding jobs. However, further investigation is needed to understand the relationships between activity and fitness in different domains. Current guidelines do not distinguish between activity during work and leisure time, so specifying leisure time recommendations by occupational physical activity level should be considered.